175k views
4 votes
If the equation is an identity or if it has no solution, write identity or no solution.

7n + 5 − 9n = 8 − 2n − 3

User Atx
by
5.1k points

1 Answer

4 votes

Answer:

7n + 5 − 9n = 8 − 2n − 3 = true

-2 n + 5 = 5 - 2 n = true

Explanation:

Left-hand side:

Simplify the following:

7 n - 9 n + 5

Grouping like terms, 7 n - 9 n + 5 = 5 + (7 n - 9 n):

5 + (7 n - 9 n)

7 n - 9 n = -2 n:

Answer: -2 n + 5

____________________________

Right-hand side:

Simplify the following:

-2 n - 3 + 8

Grouping like terms, -2 n - 3 + 8 = (8 - 3) - 2 n:

(8 - 3) - 2 n

8 - 3 = 5:

Answer: 5 - 2 n

User Pqnet
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.